Chinese herbal medicine versus antispasmodics in the treatment of irritable bowel syndrome: A network meta‐analysis. Issue 8 (4th March 2021) - Chen, Min; Qin, Di; Huang, Shi‐Le; Tang, Tai‐Chun; Zheng, Hui
Abstract: Background: Chinese herbal medicine (CHM) is gaining popularity in treating irritable bowel syndrome (IBS). Although its efficacy was shown in recent randomized controlled trials (RCTs), it is rarely compared with antispasmodics to confirm its effectiveness. We aimed to resolve this uncertainty through a network meta‐analysis. Methods: We searched for RCTs that compared CHM or antispasmodics with placebo or one of them in the treatment of IBS. The primary outcomes were adequate relief of global IBS symptoms and abdominal pain. The data were pooled using a random‐effects model. The effect size measure was pooled relative risk (RR), and treatments were ranked according to their P ‐scores. Key Results: We included 57 RCTs ( n  = 8869). After completion of treatment, drotaverine, individual CHM, otilonium, cimetropium, standard CHM, and pinaverium were efficacious in adequate relief of global IBS symptoms, and drotaverine ranked the first (RR, 2.33 [95% CI, 1.31–4.14], P ‐score =0.91); no difference was found between these treatments. After completion of treatment, drotaverine, standard CHM, pinaverium, and individual CHM were efficacious in abdominal pain, and drotaverine ranked the first (RR, 2.71 [95% CI, 1.69–4.36], P ‐score =0.91); no difference was found between these treatments. Standard CHM had significantly more adverse events than placebo (RR, 1.82 [95% CI, 1.12–2.94]) and other treatments. Conclusions: CHM and antispasmodics were efficacious for improvement of global IBS symptoms and abdominal pain. The adverse events of CHM were higher than antispasmodics; however, the heterogeneity of CHM formulas and the very low quality of the evidence warrants further investigation. Abstract : Our network meta‐analysis showed that both Chinese herbal medicine and antispasmodics were effective in treating irritable bowel diseases.